Crystal growth and aggregation in suspensions of δ-MnO2 nanoparticles: implications for surface reactivity. Issue 2 (8th January 2018) - Marafatto, Francesco Femi; Lanson, Bruno; Peña, Jasquelin
Abstract : Sodium content and suspension pH control crystallite size and aggregation in δ-MnO2 nanoparticles. Abstract : Birnessite (layer-type Mn oxide) is a key reactive phase in soils and sediments and its sorption and oxidative properties render it attractive for use in technical applications. The most widely used synthetic analog of natural and biogenic birnessite in laboratory studies is nanocrystalline δ-MnO2 . However, a wide range of physicochemical properties have been reported in the literature for δ-MnO2 . In this study, we produced several batches of δ-MnO2 and identified the mechanisms leading to significant variations in particle size, as probed by X-ray diffraction (3 to 7 nm), dynamic light scattering (85 to 501 nm) and N2 (g) BET specific surface area (SSA: 119 to 259 m 2 g −1 ) measurements. Both the coherent scattering domain (CSD) size in the ab plane and the wet-aggregate size decreased with increasing suspension pH and Na content, which is consistent with base-catalyzed oxidation and nucleation at high pH and growth by oriented attachment at low pH. The increase in the CSD size upon sample acidification but not basification provides further evidence for OA as a crystal growth mechanism. Finally, the sample SSA was not related to the crystallite size, but instead was inversely correlated to the suspension pH and Na : Mn content. The surface charge and counter-cation content of δ-MnO2 control the aggregate structure, where low pH (low Na : Mn) favored high surface area structures and high pH (high Na : Mn) favored low surface area structures. The reversibility of SSA upon the acidification or basification of parent suspensions and the crystal growth only upon suspension acidification confirmed that the primary crystallite size and the aggregate/agglomerate size are highly sensitive to solution chemistry and surface charge and has direct implications for δ-MnO2 nanoparticle reactivity towards organic and inorganic contaminants in environmental systems that can encompass a dynamic range of pH values and ionic compositions.